Phytoindication potential of dune species through predictive modeling at Jatobá beach, Barra dos Coqueiros, Sergipe - Santos, Sindiany Suelen Caduda; Souza, Rosemeri Melo (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2015)
This research aims to investigate endemic dune species able of indicate the en- vironmental situation in the area of Barra dos Coqueiros considered for creation of a conservation unit, Sergipe, starting from potential fitogeográfico revealed by modeling species distributions. Through the software Maxent were analyzed seven species endemic of dunes semifixas and incipient. The Potential distributive established for R. maritima, due to rate of dispersion near one, revealed that it is important for the recovery of coastal areas. However, I. imperati for its prediction rate near zero, is phytoindicative from fragility. The research shows that actions new need to be planned to effect real conservation of biodiversity in Sergipe.